1986
DOI: 10.1002/bip.360250209
|View full text |Cite
|
Sign up to set email alerts
|

Self‐association and solubility of peptides: Solvent‐titration study of Nα‐protected C‐terminal sequences of substance P

Abstract: SynopsisSelf-association of Na-protected peptides related to Cterminal sequences of substance P in methylene chloride was disrupted by adding increasing amounts of various polar organic solvents. This process was monitored by the disappearance of the amide I C=O stretching band (1630 cm-I ) of strongly intermolecularly H-bonded molecules in the irabsorption spectra. The effects induced by mainchain length, incorporation at position 9 of a residue promoting folding (a-aminoisobutyric acid), the nature of solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…When −Δδ/ΔT < 3 ppb K −1 the amide proton is shielded from the solvent, due to hydrogen bonding with any carbonyl oxygen atom. [91][92][93][94][95][96] The plotted −Δδ/ΔT graphs (available in the ESI ‡) for peptides and N-methylated peptides in DMSO-d 6 confirmed that no intramolecular hydrogen bonds exist for peptides 1a-4a. The presence of hydrogen bonds between the NO moiety and hydrogen-bonded NH in different N-oxide peptides 1b-4b was also investigated with this method.…”
Section: Thermal Shift Coefficient Nmr Investigation: the Nature Of Tmentioning
confidence: 71%
See 1 more Smart Citation
“…When −Δδ/ΔT < 3 ppb K −1 the amide proton is shielded from the solvent, due to hydrogen bonding with any carbonyl oxygen atom. [91][92][93][94][95][96] The plotted −Δδ/ΔT graphs (available in the ESI ‡) for peptides and N-methylated peptides in DMSO-d 6 confirmed that no intramolecular hydrogen bonds exist for peptides 1a-4a. The presence of hydrogen bonds between the NO moiety and hydrogen-bonded NH in different N-oxide peptides 1b-4b was also investigated with this method.…”
Section: Thermal Shift Coefficient Nmr Investigation: the Nature Of Tmentioning
confidence: 71%
“…Furthermore, an analysis of the thermal behaviour of hydrogen bonds in the peptides by NMR is an elegant technique to study the exact nature of this interaction. [91][92][93][94][95][96] Normally the intramolecular hydrogen bonding interaction between a hydrogen bond donor (amide proton) and an acceptor (carbonyl oxygen) in a peptide is disturbed at higher temperatures; the amide proton signals also experience a downfield shift (less through space deshielding) in the 1 H NMR spectra in aprotic solvent systems. [91][92][93][94][95][96] In aprotic solvents such as DMSO-d 6 , when −Δδ/ΔT > 5 1 ppb K −1 , the typical intramolecular peptide hydrogen bonding is absent if the amide protons are solvent-exposed.…”
Section: Thermal Shift Coefficient Nmr Investigation: the Nature Of Tmentioning
confidence: 99%
“…-A very useful probe to determine the onset of strong N-H. . .O=C H-bonds in peptides, as those typical of an intermolecular B-sheet structure and responsible for the low solubility of peptides in solvents of low polarity [14][15][16][17][18][19][20][21][22][23], is represented by the IR absorption band near 1630 cm-' assigned to the C=O stretching mode [4346]. Since in actual peptide synthesis only a small portion of the carboxyl component is converted to N-acylurea, the conclusion can be drawn that this side product should cause only a minor effect on the self-association properties of peptide chains.…”
Section: Jr-absorption Analysis Of Peptideln-acylureamentioning
confidence: 99%
“…In our peptides, both are present (1-3, [Leu9]-3 and [Leu9]-l even contain prolines). The lack of the N-terminal charge may have caused the tendency of Boc-6 to aggregate to /?-structures in CH,Cl, solution containing only small amounts of DMSO [6]. We therefore assume, in a first approximation, predominantly monomeric species in our CF,CH,OH solutions.…”
mentioning
confidence: 95%
“…Furthermore, its CD spectrum is time-dependent [3]. These studies were complemented by an IR investigation of the self-association of N(a)-protected C-terminal segments of 1 in mixtures of CH,C12 and DMSO [6]. Solventtitration studies of the 'H-NMR spectrum of Boc-Phe-Phe-Gly-Leu-Met-NH, revealed that the amide protons of Phe-7, Phe-8, Met-I I, and one proton of the primary amide group are strongly solvent-dependent, whereas the amide groups of Gly-9, Leu-10, and one proton of the primary amide group show reduced solvent accessibility (residue numbering of 1).…”
mentioning
confidence: 99%